The RELATIONSHIP BETWEEN KOWLEDGE OF DENTAL AND ORAL HEALTH MAINTENANCE BASED ON AGE AND GENDER OF JUNIOR HIGH SCHOOL STUDENTS IN MEDAN DENAI DISTRICT - Zulfi Amalia Bachtiar; Tanty Deriaty; Nurul Khofifah Nasution; Ayu Augustine Novita (Denta Journal Kedokteran Gigi, 2025)
Background: Oral and dental health play a crucial role in maintaining overall body function. Therefore, proper knowledge and behavior regarding oral hygiene are essential to ensure its preservation. Objective: This study aims to examine the relationship between oral health knowledge and the age and gender of junior high school students in the district. Materials and Methods: His study employed a correlative descriptive approach using a cross-sectional design. The sample was selected through proportional stratified random sampling with the aid of a proportion estimation formula. A total of 248 students participated, consisting of 124 from An-Nizam Middle School and 124 from Hikmatul Fadhillah Middle School. Data were collected using a 15-item questionnaire designed to assess knowledge regarding oral and dental health maintenance. The chi-square test was applied to evaluate the association between students’ oral health knowledge and their age and gender. Results: The findings revealed a significant association between knowledge levels and students’ age and gender (p < 0.05). Conclusion: The age and gender of junior high school students at Hikmatul Fadhillah and An-Nizam were found to be correlated with their understanding of personal oral health maintenance.